2020
DOI: 10.1016/j.neo.2020.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating patient-specific neoadjuvant regimens for breast cancer via a mathematical model constrained by quantitative magnetic resonance imaging data

Abstract: The ability to accurately predict response and then rigorously optimize a therapeutic regimen on a patient-specific basis, would transform oncology. Toward this end, we have developed an experimental-mathematical framework that integrates quantitative magnetic resonance imaging (MRI) data into a biophysical model to predict patient-specific treatment response of locally advanced breast cancer to neoadjuvant therapy. Diffusion-weighted and dynamic contrast-enhanced MRI data is collected prior to therapy, after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
64
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(64 citation statements)
references
References 47 publications
0
64
0
Order By: Relevance
“…However, additional experimental data is required to properly initialize and constrain a more complete description of tumor radiobiology. In the clinical setting, one potential application for this modeling framework is to predict long term response (or time to progression) to guide alternative fractionation schemes with the end goal of improving patient outcomes [ 17 , 28 ]. While short-term predictions performed well, further development may be needed to improve long term predictions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, additional experimental data is required to properly initialize and constrain a more complete description of tumor radiobiology. In the clinical setting, one potential application for this modeling framework is to predict long term response (or time to progression) to guide alternative fractionation schemes with the end goal of improving patient outcomes [ 17 , 28 ]. While short-term predictions performed well, further development may be needed to improve long term predictions.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor and vasculature growth are described using a coupled set of 3D partial differential equations built upon the reaction-diffusion model that has been extensively studied at the pre-clinical and clinical settings in glioma [ 9 , 25 , 26 , 27 ] and other tumors [ 28 , 29 ]. In our previous efforts, we have applied this model in the setting of untreated tumor growth [ 21 ] and single fraction radiotherapy [ 9 ].…”
Section: Methodsmentioning
confidence: 99%
“…The appreciation for mathematical modelling and Systems Biology in general is growing rapidly, partially due to the promising prospects of mathematical metabolic models efficacy in a wide range of applications including drug target prediction and in-silico clinical trials [238]. Although it is yet unrealistic to adopt a full-scale patient-specific model for clinical trials, patient-specific metabolic models show potential for use in evaluation of medicinal products and devices, or in prediction of the outcome of medical interventions [239] by harnessing optimization technologies including artificial intelligence (AI) to dynamically and accurately determine the required treatment [240].…”
Section: Perspectives and Challenges Aheadmentioning
confidence: 99%
“…In this section, we identify four major areas of research at the tissue scale (shown in Figure 4 ) and discuss the modeling strategy or strategies applied to these areas. Broadly, these areas include: (1) representing the evolving geometry of the tumor’s vascular network (panel a in Figure 4 ) [ 29 , 82 , 87 , 88 , 119 , 120 , 121 , 122 , 123 ], (2) estimating the associated blood flow and vascular transport of substances (panel b in Figure 3 ) [ 81 , 88 , 122 , 123 , 124 , 125 , 126 , 127 ], (3) describing the mechanisms underlying the complex interplay between tumor growth and vasculature dynamics (panel c in Figure 4 ) [ 32 , 81 , 87 , 88 , 121 , 123 , 128 , 129 ], and (4) determining the effect of cytotoxic, targeted, and anti-angiogenic therapies on the tumor-associated vascular network as well as the tumor itself (panel d in Figure 4 ) [ 28 , 85 , 86 , 124 ].…”
Section: Approaches For Modeling Tumor Vasculature and Angiogenesis At The Tissue Scalementioning
confidence: 99%
“…By employing such models, it is possible to simulate and test scenarios in silico that are not easily tested experimentally. For example, comparing the limitless number of therapeutic regimens that can be constructed with varying dosing schedules and concentrations is experimentally intractable, but with a mathematical model these can be simulated and analyzed to select the optimal regimen [ 28 ]. Recently, there has also been great interest in the modeling of tumor angiogenesis at the tissue scale [ 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%